(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In this article considering the different methods, which are taking to the account the quantitative and qualitative characteristics of human abilities and skills, suggesting the expression of the value of human capital in physical and value measurers.